Amazon web services for mobile developers : building Apps with AWS - Mishra, Abhishek (Sybex, a Wiley brand, 2018)
A practical, real-world introduction to AWS tools and concepts, this book presents a professional view of cloud computing and AWS for experienced iOS/Android developers and technical/solution architects. --